Expand

Give your answer in the form a + b√

where a and b are both integers.

where a and b are both integers.

a =

b =

b =

2

Expand

Give your answer in the form a + b√

where a and b are both integers.

where a and b are both integers.

a =

b =

b =

2

Expand

Give your answer in the form a + b√

where a and b are both integers.

where a and b are both integers.

a =

b =

b =

2

Expand

Give your answer in the form a + b√

where a and b are both integers.

where a and b are both integers.

a =

b =

b =

2

Expand

Give your answer in the form a - b√

where a and b are both integers.

where a and b are both integers.

a =

b =

b =

2

Expand

Give your answer in the form a - b√

where a and b are both integers.

where a and b are both integers.

a =

b =

b =

2

Expand

Give your answer in the form a + b√

where a and b are both integers.

where a and b are both integers.

a =

b =

b =

2

Write √2
in the form a + b√2 where a and b are both integers.

a =

b =

b =

4

Write
in the form
a + b√c

where a, b and c are all integers.

where a, b and c are all integers.

a =

b =

c =

b =

c =

4